Contractility detection of isolated mouse papillary muscle using myotronic Myostation‐Intact device. Issue 5 (27th September 2022) - Lian, Hong; Qin, Zhuyun; Wu, Mengge; Zuo, Peipei; Bai, Lina; Lu, Minjie; Li, Lulu; Zhang, Haitao
Abstract: Background: To understand the relationship between myocardial contractility and external stimuli, detecting ex vivo myocardial contractility is necessary. Methods: We elaborated a method for contractility detection of isolated C57 mouse papillary muscle using Myostation‐Intact system under different frequencies, voltages, and calcium concentrations. Results: The results indicated that the basal contractility of the papillary muscle was 0.27 ± 0.03 mN at 10 V, 500‐ms pulse duration, and 1 Hz. From 0.1 to 1.0 Hz, contractility decreased with an increase in frequency (0.45 ± 0.11–0.10 ± 0.02 mN). The voltage‐initiated muscle contractility varied from 3 to 6 V, and the contractility gradually increased as the voltage increased from 6 to 10 V (0.14 ± 0.02–0.28 ± 0.03 mN). Moreover, the muscle contractility increased when the calcium concentration was increased from 1.5 to 3 mM (0.45 ± 0.17–1.11 ± 0.05 mN); however, the contractility stopped increasing even when the concentration was increased to 7.5 mM (1.02 ± 0.23 mN). Conclusions: Our method guaranteed the survivability of papillary muscle ex vivo and provided instructions for Myostation‐Intact users for isolated muscle contractility investigations. Abstract : Lian et al. elaborated a method to detect isolated C57BL/6J mouse papillary muscle contractility under various conditions of frequencies, voltages and calcium concentration via using a new device, Myostation‐Intact. The papillary muscle is extracted from the excised heart of the mouse, then transfer to the device through a mountain aid to initiate the detection.